Effective Contract as the Factor to Govern of Work Motivation of Temporary Pedagogical Staff of the Health Camp for Children (on Example of the Federal State Budget Institution ‘Artek’) - Derkachev, P.V.; Melnik, V.P. (Psihologo-pedagogičeskie issledovaniâ, 2018)
The aim of the research is to show the reason of necessity in discovering the motivating potential of employees and also influence on them through the introduction of the effective contract. The research has studied the attitude of the temporary pedagogical staff towards the effective contract, also the research has found the factors that influence on satisfaction of labor, and the motivating profile of a personality was constructed. 207 people aged 18 - 23 have taken part in the research. Those are temporary pedagogical employees of the children's health camp. In the first part of the research the theoretical bases of the effective contract with the reference to modern literature were studied. In the second part the research has found the interrelations between being ready to work by the effective contract and outer stimuli influencing on the quality of the work performed. The revealed direct and inverse relations between the attitude to the effective contract and the reasons followed by employees give the evidence that transferring to the suggested form of labor relations can cause an absolutely opposite effect. Employees working on the effective contract will be oriented only on the remuneration in favorable working conditions and the things like self-improvement, interest to work will be of little interest for them. Целью статьи является изучение мотивационного потенциала работников через внедрение эффективного контракта. В исследовании было изучено отношение временного педагогического коллектива к эффективному контракту, выявлены факторы, влияющие на удовлетворенность трудом, и построен мотивационный профиль личности. В исследовании принимало участие 207 человек. Это педагоги детского оздоровительного лагеря в возрасте 18 – 23 года. В статье представлены теоретические основы эффективного контракта по данным современной литературы, проведено исследование и выявлены взаимосвязи между готовностью работы по эффективному контракту и внешними стимулами, влияющими на качество выполняемой работы. Установлены прямая и обратная взаимосвязи между отношением к эффективному контракту и мотивами, движущими работниками. Переход на данную форму трудовых отношений может повлечь за собой негативный эффект. Сотрудники при работе по эффективному контракту будут ориентированы только на вознаграждение при благоприятных условиях труда, и такие понятия, как самосовершенствование и интерес к работе, для них будут мало значимы.